Building The Quality Of Education In The Conflict Situations Within The Palestinian Education System - Danil, Muhammad; Ananda, Azwar; Rusdinal, Rusdinal; Gistituati, Nurhizrah (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2023)
This paper begins with an effort to build the quality of education in the Palestinian Ministry of Education's 2017-2022 Strategic Plan for Education. From these efforts, the Palestinian Ministry of Education agreed to the design of the UN 2030 Sustainable Development Goals program, especially regarding quality education. This is seen in the target to be achieved to ensure equal access by 2030 to all levels of education and vocational training for marginalized groups, including people with disabilities. Through qualitative methods, the data collection technique used is library research for primary data obtained from the Strategic Plan for Education 2017-2022 by the Palestinian Ministry of Education and news contained on websites, youtube and journals in the 2017- 2023 range. Secondary data as supporting data is obtained using relevant literature in the form of analysis results or assessment reports from government, private or research institutions. After the review, it was revealed that efforts to build the quality of Palestinian education were prioritized on three main targets: 1) Ensuring access to safe, inclusive and quality education at all levels, especially for people with disabilities; 2) Develop student-centered teaching and learning pedagogy and environment, and; 3) Improve accountability and results-based leadership, governance and management. As an implication of these efforts, there has been an increase in female student participation and completion from primary to tertiary education.